Quantum girl theory : a novel - Ryan, Erin Kate (Random House, 2022)
"On December 1, 1946, Paula Jean Weldon, a Bennington College student, disappeared. She was never found. What happened to her? Where did she go, to escape society's vision of her, and who did she become? In this riveting first novel, Erin Kate Ryan springs off from that real, unsolved case of a missing girl to imagine what might have happened to Paula Jean, to girls who decide to drop out of one life and create for themselves another one. The narrator of this mesmerizing novel is Mary, a clairvoyant detective who specializes in finding missing girls. She's a missing girl herself, and she also has the gift of "the Sight," whereby she believes she receives signals from other missing girls. She--and we--learn about the lives of six or seven different versions of who Paula Jean might have become: did she become a circus performer, a McCarthy-era informer, a murderess, a murder victim? When Mary arrives in a small Southern town in the 1960s, to find a missing girl, she discovers that in fact not one but three girls in this town are missing--a white girl, and two unreported young women who are black"--